2011
DOI: 10.1371/journal.pone.0018490
|View full text |Cite
|
Sign up to set email alerts
|

Honokiol Crosses BBB and BCSFB, and Inhibits Brain Tumor Growth in Rat 9L Intracerebral Gliosarcoma Model and Human U251 Xenograft Glioma Model

Abstract: BackgroundGliosarcoma is one of the most common malignant brain tumors, and anti-angiogenesis is a promising approach for the treatment of gliosarcoma. However, chemotherapy is obstructed by the physical obstacle formed by the blood-brain barrier (BBB) and blood-cerebrospinal fluid barrier (BCSFB). Honokiol has been known to possess potent activities in the central nervous system diseases, and anti-angiogenic and anti-tumor properties. Here, we hypothesized that honokiol could cross the BBB and BCSFB for the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
103
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(111 citation statements)
references
References 40 publications
8
103
0
Order By: Relevance
“…1A) at pharmacological doses. 14,23,26 The present study extended these finding by demonstrating dose-dependent cell viability inhibition by HNK in additional human prostate cancer cell lines, including 22Rv1 (a castration-resistant prostate cancer cell line with expression of AR splice variants) and VCaP cells (a prostate cancer cell line with wild-type AR expression), and Myc-CaP cell line derived from prostate tumor of a transgenic mouse 27 ( Fig. 1B).…”
Section: Hnk Treatment Decreased C-myc Protein Level In Prostate Cancsupporting
confidence: 70%
See 1 more Smart Citation
“…1A) at pharmacological doses. 14,23,26 The present study extended these finding by demonstrating dose-dependent cell viability inhibition by HNK in additional human prostate cancer cell lines, including 22Rv1 (a castration-resistant prostate cancer cell line with expression of AR splice variants) and VCaP cells (a prostate cancer cell line with wild-type AR expression), and Myc-CaP cell line derived from prostate tumor of a transgenic mouse 27 ( Fig. 1B).…”
Section: Hnk Treatment Decreased C-myc Protein Level In Prostate Cancsupporting
confidence: 70%
“…9 Bai et al 10 were the first to provide in vivo evidence for anticancer activity of HNK in angiosarcoma. In vivo tumor growth inhibitory effect of HNK was subsequently extended to solid tumor models, including colorectal, 11 prostate, 12 breast, 13 and brain 14 tumors. HNK or its liposomal preparation was also shown to inhibit metastasis in vivo in different preclinical models.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, honokiol has been found to improve learning and memory through preserving cholinergic neurons in the brain of senescence-accelerated prone mouse strain 8 (SAMP8) mice [14] and inhibiting the activity of acetylcholinesterase scopolamine-treated mice [15]. Importantly, Wang and colleagues have demonstrated that honokiol has the ability to cross the blood-brain barrier (BBB) [16], which enabled it to be a candidate for AD treatment. However, no study has reported the effects of honokiol in Aβ-accumulation-based cognition deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…1), isolated from the barks of Magnolia officinalis, has the ability to cross the blood-brain barrier (Wang et al, 2011). Pharmacologically, honokiol possesses diverse biological activities, including anxiolytic (Kuribara et al, 1999), analgesic (Lin et al, 2009), antidepressant (Xu et al, 2008), antithrombotic (Hu et al, 2005), antimicrobial (Ho et al, 2001), antispasmodic (Ko et al, 2003), anti-tumorigenic (Fried and Arbiser, 2009), and neuroprotective (Zhang et al, 2013) properties.…”
Section: Introductionmentioning
confidence: 99%